1991
DOI: 10.1007/bf00323775
|View full text |Cite
|
Sign up to set email alerts
|

Spring staging in Brent Geese Branta bernicla: feeding constraints and the impact of diet on the accumulation of body reserves

Abstract: The diet composition of Brent Geese Branta bernicla on a salt-marsh was quantified. Puccinellia maritima was the principal food species, while Plantago maritima and Triglochin maritima were less commonly taken. Festuca rubra only acted as a substitute for Puccinellia when production of the latter species dropped. The metabolizable energy of the food plants ranged from 5 to 11 kJ·g. By assessing the ingestion rates of geese feeding on different food species, the net intake rate could be derived. Plantago and Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
139
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(145 citation statements)
references
References 32 publications
5
139
1
Order By: Relevance
“…Brent geese prefer Puccinellia maritima in winter, Salicornia sp. leaves and seeds in autumn and Trichlogin maritima, Plantago maritima and Aster tripolium in spring (Prop and Deerenberg 1991, Summers et al 1993, Rowcliffe et al 1995, Van der Wal et al 2000. This seasonal variation in diet preference combined with effects of livestock grazing on plant-species composition could be an alternative explanation for the effects of livestock grazing in autumn and spring found in the present study.…”
Section: Effects Of Grazing Treatmentssupporting
confidence: 54%
“…Brent geese prefer Puccinellia maritima in winter, Salicornia sp. leaves and seeds in autumn and Trichlogin maritima, Plantago maritima and Aster tripolium in spring (Prop and Deerenberg 1991, Summers et al 1993, Rowcliffe et al 1995, Van der Wal et al 2000. This seasonal variation in diet preference combined with effects of livestock grazing on plant-species composition could be an alternative explanation for the effects of livestock grazing in autumn and spring found in the present study.…”
Section: Effects Of Grazing Treatmentssupporting
confidence: 54%
“…Previous studies found a positive relationship between food quality and goose grazing intensity for nitrogen concentration in green leaves below 2.4% (Prop & Deerenberg 1991), but above 3.2% (National Research Council 1994) no relationship was discovered. Meanwhile, geese prefer sites of intermediate forage quantity as their foraging efficiency drops at high sward height due to increased handling time (van de Koppel et al 1996, van der Wal et al 1998, Heuermann 2007).…”
Section: Discussionmentioning
confidence: 85%
“…Small herbivores require a higher nutrient concentration in their diets than large herbivores, as they are less capable of utilizing poor quality plants (Prins & Ydenberg 1985, Durant et al 2004, Prins & van Langevelde 2008. For instance, the Barnacle Goose Branta leucopsis requires food containing more than 15% crude protein to meet nitrogen requirements (Prop & Deerenberg 1991, Amano et al 2004. Furthermore, waterfowl have food retention times as short as a few hours (Prop & Vulink 1992, McKay et al 1994, which is reflected by a high throughput and defecation rate (Owen 1980).…”
mentioning
confidence: 99%
“…1). Nevertheless, lysine content was highest in Triglochin, a food plant known to be highly favored and quickly depleted by brent geese (Prop and Deerenberg 1991). All food plants generally showed a favorable balance, with the exception of sulphur amino acids.…”
Section: Amino Acids Of Food Plantsmentioning
confidence: 98%
“…90% (Van der Wal et al 1998). Brent goose diet in the salt marsh consists mainly of Puccinellia maritima (70-80%) supplemented by Festuca, Plantago maritima and Triglochin maritima (Prop and Deerenberg 1991). Nomenclature of food plants follows Van der Meijden (1996).…”
Section: Study Area and Sampling Of Geesementioning
confidence: 99%